The Determinant Analysis of Happiness at Work (HAW): A Systematic Literature Review - Yusuf, Faif; Suparno; Asep Dony Suhendra; Husen, Achmad (Yayasan Ilomata, 2025)
This study aims to enhance the understanding of happiness at work (HAW) by examining its dimensions and characteristics. Furthermore, it investigates the generation of knowledge concerning HAW through various theoretical frameworks, contextual elements, and methodological approaches. The study also identifies potential future avenues for HAW research. This paper undertakes a systematic literature review of 42 selected empirical articles published from 2010 to 2024, providing an in-depth exploration of HAW. It evaluates trends in publication, dimensions, characteristics, theoretical frameworks, contextual influences, and the research methodologies applied in HAW studies. The results indicate that while research on HAW has gained considerable traction, a significant need remains for further exploration, especially in developing countries. The study identifies several theoretical frameworks, including the job demand-resources model, social exchange theory, and broaden-and-build theory. It also recommends the incorporation of less frequently utilized theories, such as the positive emotion, engagement, relationships, meaning, and accomplishment (PERMA) model, alongside flow theory, for future research initiatives. This review enriches the literature on workplace happiness by providing a thorough analysis and offers valuable insights to inform future research into the factors affecting employee well-being.